CBMS-4 CHROMOSOMAL INSTABILITY IN GLIOMA USING SPECTRAL KARYOTYPING METHOD. (3rd December 2022) - Negoto, Tetsuya; Komaki, Satoru; Hashimoto, Aya; Yoshitake, Hidenori; Moritsubo, Mayuko; Furuta, Takuya; Sakata, Kiyohiko; Nakamura, Hideo; Morioka, Motohiro
Abstract: Introduction: Chromosomal instability, the cell condition in which chromosome mis-segregation occur at a high frequency during cell division, has been considered to be involved in the molecular mechanisms that give rise to the complex genetic background of glioma. However, most of this phenomenon has been based on researches using cell line, and there have been few studies of chromosomal instability in clinical specimens of gliomas. Methods: Primary cell culture was obtained from 11 glioma specimens (eight Glioblastoma (GBM), one Anaplastic PXA (aPXA), one Astrocytoma, and one Ependymoma), which was removed at our hospital, and chromosomes of up to five cells per case were analyzed by the SKY method. Chromosome instability was quantified by two parameters, one was AS (Aneuploidy score), which means the number of gain or loss of whole of the chromosome, and the other was SS: Structural abnormality score, which means the number of chromosome structural abnormality per cell. In addition, the phenotypes, which were characteristic of chromosomal instability were observed individually. Results: Each quantitative value was as follows: GBM; AS:2.30±0.51 /SS:1.64±0.38, aPXA; AS :1.40±1.33 / SS:8.20±0.99, Astrocytoma and Ependymoma; AS:0.00 /SS:0.00, suggesting that chromosomal instability was associated with GBM and aPXA. Chromosome 7 amplification was most frequent in GBM (57%), and Mosaic loss of chromosome Y was also observed in 60% of males. Some characteristic karyotypes which suggest the phenomenon of Chromothripsis or Double minute were also observed. The karyotype concordance rate in the cases with p53 mutation was 60%, and that with p53 wild type was 100%, indicating that the p53 mutation increased the genotype heterogeneity in the same specimen. Discussion: In clinical specimens of gliomas, aneuploidy and structural abnormalities were identified in GBM and aPXA, suggesting that chromosomal instability contributes to their cellular phenotype and malignancy.